Hubungan Penggunaan Media Sosial dengan Motivasi Belajar Matematika Siswa Kelas VIII SMP Negeri 6 Percut Sei Tuan - Agnes Eveline Samosir; Tiur Malasari Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
Low motivation to learn is often a serious challenge in one's academic development. Excessive use of social media can have both positive and negative impacts on learning motivation, depending on the usage policy. This study aims to analyze the magnitude of the relationship between the use of social media and the motivation to learn mathematics of class VIII students of SMP Negeri 6 Percut Sei Tuan. This study uses a quantitative approach with a correlational method. The sample consisted of 58 grade VIII students who were given video supplements related to learning materials at school through TikTok before formal learning was carried out. Based on the data analysis used using the Spearman correlation, the correlation coefficient value is + 0.744, it can be seen that the motivation to learn mathematics with the use of social media has a unidirectional relationship. This shows that if there is an increase in the value of using social media in learning, the value of math learning motivation will also increase linearly. By treating relevant learning videos through TikTok social media before learning takes place, educators are able to create a more interesting and intimate learning experience to increase student motivation in learning mathematics.